2020
DOI: 10.1101/2020.07.27.20163204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining Australian’s beliefs, misconceptions, and sources of information for COVID-19: A national online survey

Abstract: Objective: Public cooperation to practice preventive health behaviours is essential to manage the transmission of infectious diseases such as COVID-19. We aimed to investigate beliefs about COVID-19 diagnosis, transmission and prevention that have the potential to impact the uptake of recommended public health strategies. Design: An online cross-sectional survey conducted May 8 to May 11 2020. Participants: A national sample of 1500 Australian adults with representative quotas for age and gender provided by o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Among the participants, 83% held at least one COVID-19-related misconception with the most frequent being that the virus was created in a laboratory (36%). 35 …”
Section: Discussionmentioning
confidence: 99%
“…Among the participants, 83% held at least one COVID-19-related misconception with the most frequent being that the virus was created in a laboratory (36%). 35 …”
Section: Discussionmentioning
confidence: 99%
“…A local study conducted in Malaysia during the early stages of MCO found that the general public had good knowledge and positive attitudes towards the control of COVID-19, except for the practice of wearing face masks [ 19 ]. Another study in Australia reported adequate public knowledge on hand hygiene and physical distancing, but awareness on the use face mask and antibiotics remained insufficient [ 20 ]. A systematic review reported that the overall public KAP on COVID-19 was good in most countries, except a few in the initial stage of the pandemic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To correct misinformation, we should first identify what the public believes and what is right and wrong. Understanding the nature of misinformation and exploring the source of inaccurate information can promote behavior change interventions developed to solve the problem and provide accurate information [7]. Misinformation can lead to serious consequences such as increased burden on the health care system due to emergency .…”
Section: Introductionmentioning
confidence: 99%
“…To correct misinformation, we should first identify what the public believes and what is right and wrong. Understanding the nature of misinformation and exploring the source of inaccurate information can promote behavior change interventions developed to solve the problem and provide accurate information [7]. Misinformation can lead to serious consequences such as increased burden on the health care system due to emergency hospitalization caused by false beliefs or wide speared of wrong health advice, and the spread of politically motivated conspiracies like 5G masts can cause COVID-19, or the vaccine is designed to control the humanity or reduced the population; due to that, some people burnt 5G masts while others are reluctant to take the vaccine [8].…”
Section: Introductionmentioning
confidence: 99%